THE GENESIS OF CONCEPTS OF INSTITUALIZATION OF THE EU REGIONAL FINANCIAL INTEGRATION - Y. Poshtar (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with an analysis of modern theories and conceptions of monetary and financial integration in the EU. Main characteristics of the development of supranational regulation over financial markets were provided. Moreover, contemporary tendencies and perspectives of economic convergence development were defined as well.